ECONOMIC POTENTIAL OF FRENCH COMPANIES IN RUSSIAN ECONOMY - L. D. Efanova; V. L. Polyakova (Вестник университета, 2019)
The objective of the article is to substantiate the interest of French enterprises in modern Russian economy. The key Franco-Russian economic relations participants’ views on the further cooperation between countries, conclusions have been studied, conclusions and forecasts have been made. As an example, the largest French companies in Russian economy have been named and сharacterized. The main obstacles to economic integration of two countries have been designated. A historical aspect of the relationship between France and Russia, causing its mutually beneficial cooperation in our days, has been considered.